Analysis of jacking forces during pipe jacking in granular materials using particle methods - Ji, Xinbo (2020)
Trenchless technology is often used in congested urban areas or river crossings to install underground pipelines to minimize disturbance to surface traffic or other activities. Pipe jacking is a typical technique applied to jack pipe segments between two working shafts. However, the design of the jacking force is usually implemented using empirical methods. It should be emphasized that the jacking force will change for each site, depending on the magnitude of overcut, lubricants, work stoppages, geology and misalignment. A particle method is proposed to estimate the jacking force along the pipe. The microparameters are calibrated for sandy soils in Shenyang, so that the macroscale material behavior can be reproduced using the particle model. Hence, the normal force around the pipe circumference can be derived in the particle model, after which the interface friction coefficient is applied to evaluate the friction resistance mobilized at the soil-pipe interface. A modified Protodyakonov’s arch model can be used to assess the magnitude of earth pressure acting on the shield face. In the end, the combination of friction resistance and face pressure provides the jacking force. The efficacy of the proposed particle method is demonstrated by comparing calculated jacking forces with those measured in the field for three types of jacking machines in sandy soils under the Hun River, Shenyang.